EFFICACY OF CYCLOSPORINE EYE DROPS IN TREATMENT OF MEIBOMIAN GLAND DISEASE - Khan, Fatima; Khan, Summaya; Akram, Amjad; Basit, Imran; Humayun, Sadia; Rabbani, Shafaq (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the efficacy of topical cyclosporine ophthalmic solution in patients with Meibomian Gland Disease.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO), from March to May 2019.Methodology: Adult patients of 20-40 years of age, diagnosed for Meibomian Gland Dysfunction, were enrolled and divided into two groups (group A was assigned cyclosporine and group B was assigned polyvinyl alcohol povidone eye solution). Patients were instructed to administer one drop of the assigned treatment in each eye, twice daily, for 3-months. Two follow-up visits were planned for this study, first follow-up was conducted after thirty days of starting the assigned treatment while second follow-up was done at the end of three months.Results: There were total 80 patients enrolled, forty in each group. Patients were assessed for ocular signs and symptoms for Meibomian Gland Disease after one, two and three months of starting the treatment and were compared to control group. Patients belonging to cyclosporine group were found to show greater improvements in signs/symptoms of Meibomian Gland Disease including tear break up time (p 0.001 vs 0.540), Schrimer I test (p 0.001 vs 0.290), fluoresceine staining (0.007 vs 0.041), lid margin/conjunctival inflammation (0.001 vs 0.06) and Meibomian Gland expressibility (0.01 vs 0.311).Conclusion: Topical cyclosporine ophthalmic solution was found to be significantly better in resolving ocular signs and symptoms among Meibomian Gland Disease patients as compared to polyvinyl alcohol povidone.